Staging the blues : from tent shows to tourism - McGinley, Paige A. (Duke University Press, 2014)
Singing was just one element of blues performance in the early twentieth century. Ma Rainey, Bessie Smith, and other classic blues singers also tapped, joked, and flaunted extravagant costumes on tent show and black vaudeville stages. Even though folklorists, record producers, and festival promoters downplayed the theatricality of early blues in favor of notions of authenticity, virtuoso blues artists used dance, comedy, costume, and other theatrical conventions to great effect throughout the twentieth century.